Public administration and its role in civil society - Латковський, Павло Павлович; Латковський, П. П.; Латковский, Павел Павлович; Latkovskyi, Pavlo P. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The role of public administration in civil society is studied. The principles of public administration in civil society are analyzed. It is noted that the development of a modern system of public administration necessitates the introduction of new values and principles of public management in the activities of government institutions. The general principles of public administration are revealed. It is established that it is necessary to increase the efficiency of public administration at the local level, as the relationship between public administration and local economic development is the key to achieving Ukraine’s strategic goal of integration into the European space. Innovative tools of public administration in civil society are studied. It is noted that in the period of development of the information society the implementation of state functions at the appropriate level is impossible without the involvement of modern information technology systems and telecommunications networks.

Досліджено роль державного управління в громадянському суспільстві. Проаналізовано принципи державного управління в громадянському суспільстві. Зазначається, що розвиток сучасної системи державного управління зумовлює необхідність впровадження нових цінностей та принципів державного управління в діяльність державних інституцій. Розкрито загальні принципи державного управління. Встановлено, що необхідно підвищити ефективність державного управління на місцевому рівні, оскільки взаємозв’язок державного управління та місцевого економічного розвитку є запорукою досягнення стратегічної мети України – інтеграції в європейський простір. Досліджено інноваційні інструменти державного управління в громадянському суспільстві. Зазначається, що в період розвитку інформаційного суспільства реалізація функцій держави на належному рівні неможливe без залучення сучасних систем інформаційних технологій та телекомунікаційних мереж.
Latkovskyi P. P. Public administration and its role in civil society / P. P. Latkovskyi // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 114-130.
Keywords: public administration; civil society; information society; державне управління; цивільне суспільство; інформаційне суспільство; Research Subject Categories::LAW/JURISPRUDENCE::Public law